A slow fire burning [compact disc, unabridged] - Hawkins, Paula (Penguin Audio, 2021)
When a young man is found gruesomely murdered in a London houseboat, it triggers questions about three women who knew him. Laura is the troubled one-night-stand last seen in the victim's home. Carla is his grief-stricken aunt, already mourning the recent death of yet another family member. And Miriam is the nosy neighbor clearly keeping secrets from the police. Three women with separate connections to the victim. Three women who are, for different reasons, simmering with resentment. Who are, whether they know it or not, burning to right the wrongs done to them. When it comes to revenge, even good people might be capable of terrible deeds. How far might any one of them go to find peace? How long can secrets smolder before they explode into flame?